Faktor Risiko Dan Pencegahan Infeksi Multi-Drugs Resistant Organism Di Ruang Intensive Care Unit - Eppy Setiyowati; Feby Ayu Miladiya; Rudi Hartono; Zubaidi Zubaidi (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: MDRO is a significant problem in healthcare, particularly in the ICU. MDRO infections have a poorer prognosis and even death in ICU patients. The aimed of this study was to identify risk factors and prevention of MDRO in ICU patients. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through the following databases: Pubmed, Sciencedirect, and Scopus for studies published from 2021-2025 that report risk factors and prevention of MDRO in ICU patients. Results: Data from 1,357 articles resulted in 10 articles identified according to the inclusion criteria. The sample obtained was 10,969 ICU patients. Identified risk factors for MDRO infection were length of stay, antibiotic use, and patient clinical condition. Meanwhile, prevention measures include screening, antibiotic control, prevention of healthcare infections, and strengthening environmental hygiene practices and hand hygiene. Conclusion: Risk factors for MDRO infection can be prevented by early patient screening as well as standard precautions and contact precautions in all treatment rooms, especially in the ICU. Keywords: Multidrugs-resistant organisms (MDRO), Intensive Care Unit (ICU), Risk factor, prevention